Estudio de la coordianción de las protecciones por métodos computarizados aplicados al centro comercial ríocentro sur - Coloma, Víctor (2009)
This study addresses an important field in the desing of an electrical system either commercial or industrial, this is the cordination of the electrical protection. The coordination of the protection depends on good or bad power system operation